Utilização de tecnologias computacionais para aperfeiçoamento da prestação jurisdicional extrajudicial no poder judiciário do Tocantins - Varão, Harly Carreiro (Universidade Federal do Tocantins, 2020)
The Tocantins Court of Justice (TJTO) has achieved high levels of computerization of its processes, whether in the judicial or extrajudicial areas. This scenario brings with it the need for transparency in carrying out such procedures, as well as the engagement of the Tocantins citizen. With regard to extrajudicial service, intensifying access to information and analyzing data resulting from inspections of extrajudicial services are aspects that need attention. In this sense, the objective of this research is to analyze the data resulting from in-person extrajudicial corrections using data mining and to decentralize access to extrajudicial information through a mobile solution, both aiming at the transparency of the acts practiced by Tocantins extrajudicial services. As a result, the research will bring up resources that may be essential for the guidance, control and inspection of extrajudicial services.